German banks – a declining industry? - Andreas Hackethal (Goethe University Frankfurt, Center for Financial Studies (CFS), 2003)
This paper is a draft for the chapter German banks and banking structure of the forthcoming book The German financial system edited by J.P. Krahnen and R.H. Schmidt (Oxford University Press). As such, the paper starts out with a description of past and present structural features of the German banking industry. Given the presented empirical evidence it then ar-gues that great care has to be taken when generalising structural trends from one financial system to another. Whilst conventional commercial banking is clearly in decline in the US, it is far from clear whether the dominance of banks in the German financial system has been significantly eroded over the last decades. We interpret the immense stability in intermedia-tion ratios and financing patterns of firms between 1970 and 2000 as strong evidence for our view that the way in which and the extent to which German banks fulfil the central functions for the financial system are still consistent with the overall logic of the German financial sys-tem. In spite of the current dire business environment for financial intermediaries we do not expect the German financial system and its banking industry as an integral part of this system to converge to the institutional arrangements typical for a market-oriented financial system.
urn:nbn:de:hebis:30-10320
Keywords: G21; G23; 330; commercial banking; Germany; disintermediation; financial system